2003
DOI: 10.1002/anie.200300573
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur and Selenium: The Role of Oxidation State in Protein Structure and Function

Abstract: Sulfur and selenium occur in proteins as constituents of the amino acids cysteine, methionine, selenocysteine, and selenomethionine. Recent research underscores that these amino acids are truly exceptional. Their redox activity under physiological conditions allows an amazing variety of posttranslational protein modifications, metal free redox pathways, and unusual chalcogen redox states that increasingly attract the attention of biological chemists. Unlike any other amino acid, the "redox chameleon" cysteine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
375
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 711 publications
(386 citation statements)
references
References 129 publications
(148 reference statements)
7
375
0
4
Order By: Relevance
“…Figure 3 shows the spectra of selected organic reference compounds, where one can notice that the position of the white line is similar for all compounds (except the second peak of the oxy-myoglobin, that comes from sulphate ligand). The results, presented in Table I, are consistent with the literature [9][10][11][12]. As should be noticed, there is a difference between formal and apparent oxidation state, received from XANES measurements, for example the apparent oxidation states of sulphur in thiosulphates, obtained from XANES data, are −1 and +5, while the formal ones are −2 and +6.…”
Section: Determination Of Oxidation States Of Sulphursupporting
confidence: 89%
“…Figure 3 shows the spectra of selected organic reference compounds, where one can notice that the position of the white line is similar for all compounds (except the second peak of the oxy-myoglobin, that comes from sulphate ligand). The results, presented in Table I, are consistent with the literature [9][10][11][12]. As should be noticed, there is a difference between formal and apparent oxidation state, received from XANES measurements, for example the apparent oxidation states of sulphur in thiosulphates, obtained from XANES data, are −1 and +5, while the formal ones are −2 and +6.…”
Section: Determination Of Oxidation States Of Sulphursupporting
confidence: 89%
“…In fact, 5 of the cysteines are predicted to be surface-exposed. Sulfur in cysteine can adopt several redox states, and Cys is therefore involved in a number of functions and it is a common site for posttranslational modifications 31 . In the case of mouse SR, Mustafa et al 27 have shown that modification at C113 can prevent ATP binding and activation.…”
Section: Thermal Stability Of C217s K221e and S84g/p111l Hsrmentioning
confidence: 99%
“…5 The thiol and thioether groups are part of amino acids and their oxidation by metal ions has been studied for decades because of their important role in both the structure and function of proteins. 6 Oxidatively modified proteins accumulate during aging, oxidative stress and in age-related diseases, and some of them were found in liver, heart, skeletal muscle, kidney, and in regions of the brain. 5 L-Cysteine, L-methionine and the tripeptide glutathione (GSH, γ-glu-cys-gly) contain at least three potential donor groups, viz.…”
Section: Introductionmentioning
confidence: 99%